Tinjauan Etika Profesionalisme It Dalam Pemanfaatan Big Data Untuk Sistem Business Intelligence - Muhamad Arghi Trianda Vianuri; Evy Nurmiati (Journal Of Informatics And Busisnes, 2026)
Big Data-based Business Intelligence (BI) systems have evolved into autonomous profiling and decision-making engines, triggering ethical dilemmas and privacy violation risks. This study aims to analyze the intersection between Information Technology (IT) professionalism ethics, BI architectural implementation, and compliance with Law Number 27 of 2022 concerning Personal Data Protection (UU PDP). Utilizing a Design Science Research (DSR) approach combined with a normative-juridical review, this study evaluates software engineering practices through data exploitation case studies in Indonesia. The results indicate that the UU PDP mandate and international codes of ethics demand the proactive adoption of Privacy by Design (PbD) and Data Protection Impact Assessment (DPIA) starting from the requirement analysis phase. As a practical contribution, this research proposes the Ethically-Aligned Business Intelligence (E-BI) framework featuring a five-layer architecture to integrate ethical controls, ensuring BI systems operate fairly, transparently, and respect data subjects' rights.